2000
DOI: 10.4315/0362-028x-63.6.807
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Foodborne Illnesses Reported by the Foodborne Diseases Active Surveillance Network (FoodNet)—1997

Abstract: In 1997, the Foodborne Diseases Active Surveillance Program (FoodNet) conducted active surveillance for culture-confirmed cases of Campylobacter, Escherichia coli O157, Listeria, Salmonella, Shigella, Vibrio, Yersinia, Cyclospora, and Cryptosporidium in five Emerging Infections Program sites. FoodNet is a collaborative effort of the Centers for Disease Control and Prevention's National Center for Infectious Diseases, the United States Department of Agriculture's Food Safety and Inspection Service, the Food and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 1 publication
3
42
1
1
Order By: Relevance
“…Foodborne diseases are among the most serious public health concerns all over the world and are a major cause of morbidity (Wallace et al, 2000). Its incidence has been increased considerably during the last decades by the rapid globalisation of the food market, the increase of person and food transports, and the profound changes in the food consumption habbits (Käferstein et al, 1997).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Foodborne diseases are among the most serious public health concerns all over the world and are a major cause of morbidity (Wallace et al, 2000). Its incidence has been increased considerably during the last decades by the rapid globalisation of the food market, the increase of person and food transports, and the profound changes in the food consumption habbits (Käferstein et al, 1997).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Very few studies have examined the possible relationship at the neighborhood level between food access and microbial food safety despite shared sociodemographic risk factors related to both access and food borne infections (Wallace et al, 2000;Hardnett et al, 2004). Koro et al (2010) and Signs et al (2011) reported that ready to eat foods and fresh produce purchased in stores in low SES areas of Philadelphia had higher plate counts of yeast, mold, and bacteria (total aerobes, anaerobes, and coliforms) as compared to the same items purchased in higher SES areas.…”
Section: Introductionmentioning
confidence: 99%
“…Because food products are now often sold in areas of the world far distant from their site of production, the need for extended shelf life for these products has also increased. Studies have shown that the outbreaks caused by food borne microorganisms are epidemiologically linked to the consumption of several foods like meat, dairy products, poultry, fruits, chocolate and vegetables (Wallace et al, 2000). Food preservation is the best known approach against preventing such microbial contamination/spoilage in food, and over the years chemical preservatives have been used in for this purpose.…”
Section: Introductionmentioning
confidence: 99%